2016
DOI: 10.1016/j.chemosphere.2016.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic (III, V), indium (III), and gallium (III) toxicity to zebrafish embryos using a high-throughput multi-endpoint in vivo developmental and behavioral assay

Abstract: Gallium arsenide (GaAs), indium gallium arsenide (InGaAs) and other III/V materials are finding increasing application in microelectronic components. The rising demand for III/V-based products is leading to increasing generation of effluents containing ionic species of gallium, indium, and arsenic. The ecotoxicological hazard potential of these streams is unknown. While the toxicology of arsenic is comprehensive, much less is known about the effects of In(III) and Ga(III). The embryonic zebrafish was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…However, it is still not known whether the chorion is also a barrier to the transport of chlorinated anilines. Still, the present study and previous reports (Kim & Tanguay, ; Olivares et al ., ) suggest the possibility of miscalculated mortalities in studies assessing the environmental risk of chemicals conducted only during embryogenesis, as mortality rates apparently differ in the larval stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still not known whether the chorion is also a barrier to the transport of chlorinated anilines. Still, the present study and previous reports (Kim & Tanguay, ; Olivares et al ., ) suggest the possibility of miscalculated mortalities in studies assessing the environmental risk of chemicals conducted only during embryogenesis, as mortality rates apparently differ in the larval stage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, toxicity testing using fish embryos has been recommended as a more humane form of animal testing (EU, ). However, we previously demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals (Horie, Yamagishi, Koshio, Iguchi, & Tatarazako, ; Horie, Yamagishi, Takahashi, et al, ), possibly because the chorion blocks the transport of certain chemical compounds (Kim & Tanguay, ; Olivares, Field, Simonich, Tanguay, & Sierra‐Alvarez, ). The results of the present study suggest that triclosan exposure negatively affects both the embryonic and the early larval stage in Japanese medaka, with a particularly steep increase in mortality soon after hatching, which is consistent with previous reports of delayed mortality in zebrafish exposed to the dioxin‐like pollutant PCB‐126 (3,3′,4,4′,5‐pentachlorobiphenyl) (Di Paolo et al, ) or to chlorinated anilines (Horie, Yamagishi, Koshio, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout arsenic exposure, the chorion was left on (until a natural hatch between 48 and 72 hpf) so that the study was more biologically relevant. Although the chorion has been shown to reduce some transfer of arsenic to the embryo, arsenic is still able to pass through (Olivares, Field, Simonich, Tanguay, & Sierra‐Alvarez, ).…”
Section: Methodsmentioning
confidence: 99%